MANAGING THE HALAL INDUSTRY AND THE PURCHASE INTENTION OF INDONESIAN MUSLIMS: The Case of Wardah Cosmetics (State Islamic University (UIN) of Sunan Ampel Surabaya, 2019)
The issue on halal currently becomes a global trend. As a matter of fact, it has also become the lifestyle of Muslims around the world including Indonesia, a country with the largest Muslim population. One interesting phenomenon in Indonesia in relation to the halal industry is Wardah Cosmetics. This brand can be called as the pioneer of halal cosmetics in Indonesia. It promotes itself with three taglines; pure and safe, beauty expert, and inspiring beauty. Unfortunately, Wardah has not yet achieved its optimal potential as there are still negative responses towards the quality of Wardah products. In addition, the distribution of Wardah products are still segmented in urban areas only. Despite the fact, Wardah still is a good showcase of the success of halal industry particularly the cosmetics industry as it succeed to position itself as one the leading brands in Indonesia. This paper finds that the strategy and mechanisms of the halal industry run by wardah cosmetics have been closely connected to the purchase intention of the Indonesia Muslims.